2020
DOI: 10.1101/2020.06.01.127639
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Envelope Glycoprotein Assembly from Old-World Hantaviruses in the Golgi Apparatus of Living Cells

Abstract: 13Hantaviruses are emerging pathogens that occasionally cause deadly outbreaks in the human 14 population. While the structure of the viral envelope has been characterized with high precision, 15 the protein-protein interactions leading to the formation of new virions in infected cells are not 16 fully understood yet. In this work, we use quantitative fluorescence microscopy (i.e. 17 Number&Brightness analysis and fluorescence fluctuation spectroscopy) to quantify the 18 interactions that lead to oligome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Therefore, in order to quantify protein-protein interactions directly at the PM of living cells, we performed fluorescence fluctuation spectroscopy experiments under physiological conditions. Such experimental approaches (i.e., sF(C)CS and (cc)N&B) provide information regarding the oligomeric state, surface concentration, hetero-interactions and dynamics in complex biological systems (51,52,(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in order to quantify protein-protein interactions directly at the PM of living cells, we performed fluorescence fluctuation spectroscopy experiments under physiological conditions. Such experimental approaches (i.e., sF(C)CS and (cc)N&B) provide information regarding the oligomeric state, surface concentration, hetero-interactions and dynamics in complex biological systems (51,52,(63)(64)(65)(66).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the formation of very large multimers of M1-mEGFP in infected cells might be partially due to i) higher M1 concentrations at the PM or ii) the presence of unlabeled M1 molecules which more efficiently support protein-protein interactions. It was in fact reported that fluorescent viral proteins might not be able to oligomerize on a very large scale (65). Alternatively, other viral proteins or altered lipid metabolism (and, consequently, modification of PM composition) in infected cells might play a role and these possibilities are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%